AB0859 Similarities and differences between non-radiographic and radiographic axial spondyloarthritis in proof china cohort. (12th June 2018) - Huang, F.; Bao, C.; Fang, Y.; Wu, L.; Jiang, L.; He, D.; Xu, J.; Zhang, F.; Zhang, X.; Bi, L.; Hojnik, M.; Poddubnyy, D.
Abstract : Background: National observational studies, mostly from Europe, have reported some differences between radiographic axial spondyloarthritis (axSpA) and non-radiographic axSpA (nr-axSpA). Objectives: To compare demographic and clinical characteristics of patients (pts) with nr-axSpA and radiographic axSpA (ankylosing spondylitis, AS) in a Chinese subpopulation in the PROOF study. Methods: PROOF is a prospective observational study evaluating clinical and radiographic outcomes in axSpA pts in rheumatology clinical practice in 29 countries over 5 years. Pts diagnosed ≤1 year before study enrollment with axSpA fulfilling ASAS classification criteria were eligible. Investigator confidence with the axSpA diagnosis was ascertained on a numeric rating scale (0–10) at enrollment and end of follow-up. Baseline characteristics are reported, including demographics and clinical characteristics (table 1). Classification as nr-axSpA or AS was according to the radiologic criterion of the modified New York criteria. If there was a disagreement in classification (nr-axSpA or AS) between a local and central reader, the radiograph was evaluated by a second central reader, who was blinded to previous assessments; the final classification was based on the decision of 2 of 3 readers. Results: 464 (21.8%) pts in PROOF were enrolled in China; 307 (66.2%) were classified as AS and 157 (33.8%) as nr-axSpA according to the investigators. Confidence with the axSpA diagnosis was 9.0±1.5. The final classification based on central assessment of sacroiliac radiographs was confirmed in 372 (80%) pts included in further analyses; 301 pts (80.9%) were classified as AS and 71 (19.1%) as nr-axSpA. AS pts had longer time since diagnosis, more frequent and higher CRP elevations, and were more often male and treated with TNF inhibitors (table 1). HLA-B27 positivity and prevalence of other SpA features were comparable between the 2 groups. Most disease burden assessments were comparable, but ASDAS-CRP, BASFI, and SF-12v2 physical component score were higher in AS pts (table 1). Conclusions: Clinical features and disease burden were generally similar between nr-axSpA and AS pts in the Chinese PROOF subpopulation. AS pts were more frequently men, had higher inflammatory burden (CRP and ASDAS-CRP), more functional impairment, and were more frequently treated with TNF inhibitors. Acknowledgements: AbbVie funded the study and analysis, and approved the abstract for submission. Medical writing support was provided by Wendy Gloffke, PhD, of Complete Publication Solutions, LLC (North Wales, PA, USA), and was funded by AbbVie. Disclosure of Interest: F. Huang: None declared, C. Bao: None declared, Y. Fang Consultant for: AbbVie and Pfizer, Speakers bureau: AbbVie and Pfizer, L. Wu Consultant for: AbbVie, Speakers bureau: AbbVie, L. Jiang: None declared, D. He: None declared, J. Xu: None declared, F. Zhang Consultant for: AbbVie, Speakers bureau: AbbVie, X. Zhang: None declared, L. Bi: None declared, M. Hojnik Employee of: AbbVie, D. Poddubnyy Grant/research support from: AbbVie, Janssen, MSD, Novartis, Pfizer, Consultant for: AbbVie, BMS, Boehringer, MSD, Novartis, Pfizer, and UCB, Speakers bureau: AbbVie, BMS, Janssen, MSD, Novartis, Pfizer, Roche, and UCB